TRANSAMINASE AND BILIRUBIN LEVELS AS PREDICTORS OF CHOLESTASIS MORTALITY RELATED TO NEONATUS SEPSIS - rokhayati, evi; sebastian, reza (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2025)
Sepsis-associated cholestasis itself has a mortality rate of 52.8% in neonates. This high mortality rate is accompanied by the absence of methods in predicting death due to sepsis-related cholestasis. This study aims to determine the role of transaminase and bilirubin levels in predicting the death of patients with sepsis-associated cholestasis in neonates. Analytic observational research study with a cross sectional approach at Dr. Moewardi Hospital. Samples were obtained from the medical records of patients with cholestasis related to neonatal sepsis from 2020-2022. Bilirubin and transaminase statistically analyzed using ROC curves and logistic regression multivariate analysis. Of the 85 samples, 48 (56.5%) male patients and 37 (43.5%) female patients were obtained. In the analysis with the ROC curve, it was obtained for total bilirubin cut-off 10.13 mg/dl, direct bilirubin obtained cut-off 6.7 mg/dl, and indirect bilirubin obtained cut-off 3.62. AST had a cut-off of 49.5 IU/L and ALT had a cut-off of 30.5. In multivariate analysis, the direct bilirubin level had a p value of 0.001 with an adjusted OR of 10.93 and the AST level had a p value of 0.000 with an adjusted OR of 19.73. Direct bilirubin and AST levels can predict mortality in patients with neonate sepsis-associated cholestasis.